THE EFFECTIVENESS OF APPLICATIONS OF BETEL (Piper Betel Linn.) LEAF EXTRACT AND BACTERIOCIN FOR TEAT DIPPING DURING MILKING HANDLING IN INDONESIAN DAIRY FARMING - Komala, Iyep; Arief, Irma Isnafia; Atabany, Afton; ENSD, Lucia Cyrilla (Malaysian Journal of Science, 2023)
This study aims to investigate the effectiveness of teat dipping using sirih leaf extract (Piper betle) and bacteria in dairy farms located in Cijeruk Subdistrict, Bogor Regency, West Java. The research employs an experimental design utilizing a Completely Randomized Design (CRD) with four treatments: (1) teat dipping with masofilm (2% iodine) as the positive control, (2) teat dipping with bacteriocin (protein content = 11.17 g mL-1) (P1), (3) teat dipping with betel leaf extract (25% concentration-based) (P2), and (4) teat dipping without any additional treatment, serving as the negative control. Each treatment is replicated three times. The observed parameters include the reduction in somatic cell count (SCC) and total plate count (TPC) in cow's milk. Data were collected through sampling from 12 cows and analyzed using milk quality analysis to assess the conditions of dairy farms in Cijeruk Subdistrict.